2020
DOI: 10.1534/g3.120.401249
|View full text |Cite
|
Sign up to set email alerts
|

A Set of Diverse Genes Influence the Frequency of White-Opaque Switching in Candida albicans

Abstract: The fungal species Candida albicans is both a member of the human microbiome and a fungal pathogen. C. albicans undergoes several different morphological transitions, including one called white-opaque switching. Here, cells reversibly switch between two states, "white" and "opaque," and each state is heritable through many cell generations. Each cell type has a distinct cellular and colony morphology and they differ in many other properties including mating, nutritional specialization, and interactions with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…Here, we report that the putative PKA phosphorylation of residue T208 on the transcriptional regulator Efg1 increases white-to-opaque switching rates and that exposure to submicromolar concentrations of (E,E)-farnesol decreases white-to-opaque switching rates in C. albicans. Farnesol did not affect the reverse transition, opaque-to-white switching rates (at 25˚C on glucose), a unidirectional effect that had been observed previously for other mutations and environmental conditions [23,64,65]; these results further underscore the independence of the mechanisms for the establishment versus the maintenance of the opaque cell type. Unlike the yeast-to-hyphal transition, where farnesol's negative effects are mediated by Czf1, we found that Czf1 was not required for farnesol to affect white-to-opaque switching, suggesting that the two effects are mediated, at least in part, through different signaling pathways.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Here, we report that the putative PKA phosphorylation of residue T208 on the transcriptional regulator Efg1 increases white-to-opaque switching rates and that exposure to submicromolar concentrations of (E,E)-farnesol decreases white-to-opaque switching rates in C. albicans. Farnesol did not affect the reverse transition, opaque-to-white switching rates (at 25˚C on glucose), a unidirectional effect that had been observed previously for other mutations and environmental conditions [23,64,65]; these results further underscore the independence of the mechanisms for the establishment versus the maintenance of the opaque cell type. Unlike the yeast-to-hyphal transition, where farnesol's negative effects are mediated by Czf1, we found that Czf1 was not required for farnesol to affect white-to-opaque switching, suggesting that the two effects are mediated, at least in part, through different signaling pathways.…”
Section: Discussionsupporting
confidence: 76%
“…Neither 0.1 μM nor 1 μM farnesol affected the reverse switching rate, that is switching of opaque cells to white cells (Table 1). The unidirectional nature of farnesol's effect is similar to that of many of the gene deletions and environmental signals that affect white-opaque switching, and is consistent with the apparent independence of the mechanisms for the establishment and maintenance of the opaque cell type [23,64,65].…”
Section: Submicromolar Farnesol Exposure Inhibits White-to-opaque Swi...supporting
confidence: 61%
See 1 more Smart Citation
“…A variety of genes ( 43 ) encoding signaling proteins ( 35 , 36 , 38 ), trans -acting factors ( 12 , 39 , 40 ), and chromatin modulation factors ( 11 , 41 , 42 ) play roles in regulating switching from white to opaque. Central to many of the proposed regulatory models are the two TFs.…”
Section: Discussionmentioning
confidence: 99%